PARADOKS MODERNISASI VIS A VIS DEHUMANISASI DALAM PENGELOLAAN KEUANGAN DESA - Ramadhan, Puja Rizqy; Panggabean, Fitri Yani; Lubis, Nia Pratiwi (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2023)
This study aims to reconstruct village financial management using modernity vis a vis dehumanizaton perspective. This study uses primary data obtained from observations and interviews with informants. The research approach used is a qualitative method. The research paradigm uses the paradigm of criticism with data collection procedures, data presentation, data reduction and conclusion/verification. The results showed that the modernization and digitization of financial management in Klambir V Kebun Village had an impact on social relations in the community, which became less harmonious. For this reason, it is necessary to carry out an accounting reconstruction based modernity vis a vis dehumanizaton perspective that is relevant to be carried out in Klambir V Kebun Village.